Forage biomass estimated with a pre-calibrated equation of a rising platemeter in pastures grown in tropical conditions - Villalobos Villalobos, Luis Alonso (2023)
Accurate estimates of forage biomass allow for better adjustments of stocking rate, carrying capacity, and dry matter intake in livestock operations. Among the most common methods to estimate biomass are platemeters, for which specific calibration equations have been developed for temperate conditions. However, platemeters are not commonly used in tropical livestock operations where their goodness of fit to estimate forage biomass remains unknown. In this study, we aimed to compare three methods (the rising platemeter, Botanal®, and hand-clipping) to estimate forage biomass throughout one year on perennial ryegrass (Lolium perenne), Kikuyu (Cenchrus clandestinus), and African stargrass (Cynodon nlemfuensis Vanderyst) pastures in Costa Rica. Estimates of forage biomass were consistently greater with the platemeter than with the Botanal® and clippings across the three grass species evaluated. In Ryegrass pastures, the residual standard deviation (1845 kg DM ha−1) of forage biomass estimated with the platemeter was two- and four-fold with respect to Stargrass and Kikuyu pastures (935 and 447 kg DM ha−1), respectively. Although platemeters are straightforward methods for biomass estimation in pastures, our data suggest that their use and implementation in tropical pastures may lead to overestimating indicators such as stocking rate and carrying capacity. We suggest developing calibration equations specific for tropical conditions that consider our findings as an input to adjust the sampling procedure necessary to improve the accuracy of platemeters and foster greater adoption among livestock producers.